An overview of medical applications of montmorillonite clay - Hassen, Jasim Hamadi; Abdalkadir, Hamad Kalefa; Abed, Saher Faiq (Journal of Medical Science, 2023)
Clays are among the most important material available in nature. Montmorillonite MMT is an important type of clay mineral whose physical structure is typically perceptible as layers and sheets. Each layer is made up of one octahedral and two tetrahedral structural sheets. Due to its distinctive properties, such as swelling and adsorption, MMT has been used in a variety of industrial and therapeutic applications. The high adsorption capacity of MMT contributes to increasing drug intercalation and then its sustained release. By strongly adhering to the drug, MMT typically maintains drug release in many formulations and speeds up the solubility and bioavailability of hydrophobic drugs. MMT has also been used to develop composite delivery systems that combine it with other polymer-based materials. MMT could therefore be used to develop a variety of drug delivery systems to regulate and enhance a drug’s pharmacological qualities, such as solubility, dissolution rate, and absorption. An important note to mention is that clays in general are traditionally considered bio-inert or even biocompatible. In this review, the distinguished applications of MMT clay as an agent in the medical field were discussed. Among those applications is its use as an antibacterial agent, detoxification agent, preventive obesity agent, drug carrier agent, and in the treatment of cancer, diarrhea, wounds, and bones.